EVALUASI TORSI ELECTRIC ENGINE PROTOTIPE PERAHU LISTRIK NELAYAN MENGGUNAKAN METODE PRONY BRAKE - Ramadhani, Ahmad Ilham; Murtono, Andie (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
Fishing boat technology utilizing an electric motor drive system has been developed as one of the innovations in marine vehicle design. Electric boats can move using the torque force generated from the electric motor to rotate the motor shaft, which is connected to the propeller. The aim of this research is to evaluate the torque force produced by an electric engine using the prony brake method. The research method employed was an experimental approach, focusing on variations in load, external diameter of the motor shaft pulley, and motor rotation. The results of experimental calculations show that the prony brake test can be used as an instrument in the approach method for calculating torque. The torque value is influenced by the pulley diameter and load variations. The largest torque value for variations in load and pulley diameter is at a pulley diameter of 3 inches and a load of 8 kg, namely 3.10 Nm. Changes in motor shaft rotation (rpm) affect the increase in torque. The largest torque value in the rotation variation is at 800 rpm and a load of 8kg for each diameter variation; 4.31 Nm (2 inches), 5.34 Nm (2.5 inches), 6.46 Nm (3 inches). The torque obtained is used as a reference in determining the capabilities of the electric engine and the capabilities of the fishing boat prototype while operating at sea.